Effect of 805 nm on reliability of 735/805/850-nm LED involved near-infrared spectroscopy biomedical device. (November 2017) - Zhao, Yue; Qiu, Lina; Zhao, Ke; Li, Kai; Sun, Yunlong; Meng, Lingkang; Huang, Zhe; Li, Ting
Abstract: Near-infrared spectroscopy (NIRS) has been widely used in biomedicine due to its capability of noninvasively detecting hemodynamic variations in relative deep tissue. Most NIRS devices utilized multiple-wavelengths integrated LED as the sources, of which the 735/805/850-nm LED was mostly employed. As we known, the 735/850-nm combination is enough for quantifying the changes of oxy-hemoglobin (∆ HbO2 ) and deoxy-hemoglobin (∆ Hb). Then how is the effect of the wavelength 805 nm of 735/805/850-nm LED on the measurement reliability? Here we performed blood model experiments with 57 human blood samples and recorded optical density variations at above 3 wavelengths. Both of the least squares method and multi-variable linear regression analysis were used to quantify ∆ HbO2 and ∆ Hb with three-wavelength combination (735/805/850-nm) and two-wavelength combination (735/850-nm) respectively. By comparing the quantified values with the real values, we found that the results obtained from 735/850-nm combination are more close to reality than the 735/805/850-nm combination. This study reported, for the first time, that 805 nm actually took a negative effect on measurement reliability of NIRS. It indicates to get rid of 805 nm from such LED design to reduce the LED cost and get higher reliability for NIRS instrumentation. Highlights: First time to report the negative effect of 805 nm on 735/805/850-nm LED embedded NIRS measurement reliability. Large-sample human blood model experiments and multi-method analysis to study the effect of 805 nm on NIRS reliability. First to suggest getting rid of 805 nm to reduce LED cost and earn higher reliability for NIRS device.